KORELASI ANTARA MOTIVASI DAN GAYA BELAJAR DENGAN NILAI KOGNITIF PADA PEMBELAJARAN TEMATIK KELAS IV - Trioktaviani Aling; Tahmid Sabri; Dyoty Auliya Vilda Ghasya (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the correlation between learning motivation andlearning style with students' cognitive values in the fourth grade thematiclearning at State Elementary School 03 South Pontianak. The research methodused is descriptive method in the form of relationship studies by using correlationstudies. The population in this study amounted to 129 students and the sampleused was class IV D totaling 32 students. Data collection techniques in this studyare direct communication techniques, indirect communication techniques anddocumentary study techniques. The instruments (data collection tools) of thisstudy were interviews (interviews), questionnaires (questionnaires) and cognitivevalue documents. The results showed that students' learning motivation at theState Elementary School 03 South Pontianak was 83.94% in the